Sandheden og den usynlige hånd - Kappel, Klemens (Politik, 2014)
The paper discusses a version of laissez-faire regarding freedom of speech and public debate according to which truth will prevail in a free and open exchange of views, which is one important reason there should be no restrictions on freedom of speech, and why we should reject restraining social norms regulating the exchange of views. e paper argues that this view is far too optimistic by considering various interpretations of the idea that a free and open exchange of ideas is conducive to truth. is analysis suggests that the desir- able epistemic e ects of deliberation are deeply dependent on a su cient proportion of deliberators comply- ing with norms for proper deliberation, that is norms requiring sincerity, truthfulness, openness and so on. e paper nally considers the nature of this form of regulation of our deliberation and speech behaviour.